A Case Study of Secularism in Nepal (Voice of Teacher, 2022)
Secularization has constituted the centerpiece of the sociology of religion indecent years. It is argued that this controversy is a particularly important and illuminating site upon which the redirection of the sociological enterprise is being wrought. So far, secularism been seen as an opportunity for religious minorities to claim equal support. The state is given the active duty to enhance and reform religious traditions. The emerging form of Nepalesesecularism may not merely contribute to a rethinking of the Western categories of the secular; its continuing evolution may also be most instructive for western countries. The objectives of the research are to know the emergence of secularism in Nepal and to evaluate the consequences of secularism in Nepal. In this paper, I have focused on the debate of secularism in Nepal. Here, I have applied the qualitative methods with case studies. The respondents were selected through purposive sampling. The aim here is to offer a perspective from which to begin to analyze the formation of Nepalese secularism, and the forces which are presently shaping it.